2023
DOI: 10.3389/fimmu.2023.1000497
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages respond to chemotherapy by detrimental transcriptional reprogramming and suppressing stabilin-1 mediated clearance of EGF

Abstract: IntroductionTumor resistance to chemotherapy and metastatic relapse account for more than 90% of cancer specific mortality. Tumor-associated macrophages (TAMs) can process chemotherapeutic agents and impair their action. Little is known about the direct effects of chemotherapy on TAMs.MethodsThe effect of chemotherapeutic platinum agent cisplatin was assessed in the model system of human ex vivo TAMs. Whole-transcriptome sequencing for paired TAMs stimulated and not stimulated by cisplatin was analysed by NGS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Thus outcome of different SR activities will be the decision of monocytes and macrophage to guard homeostatic balance, or to create chronic inflammatory microenvironment that frequently is further complicated by fibrosis ( 56 ). Scavenger receptor on macrophages play an essential role in clearing and removing not only of cellular debris, apoptotic cells, but also fibrin, and growth factors, including epithelial growth factor (EGF) and GDF-15 ( 55 , 60 62 ). To carry out this analysis, an in vitro endocytosis or phagocytosis tests can be used.…”
Section: Implant Materials and Inflammationmentioning
confidence: 99%
“…Thus outcome of different SR activities will be the decision of monocytes and macrophage to guard homeostatic balance, or to create chronic inflammatory microenvironment that frequently is further complicated by fibrosis ( 56 ). Scavenger receptor on macrophages play an essential role in clearing and removing not only of cellular debris, apoptotic cells, but also fibrin, and growth factors, including epithelial growth factor (EGF) and GDF-15 ( 55 , 60 62 ). To carry out this analysis, an in vitro endocytosis or phagocytosis tests can be used.…”
Section: Implant Materials and Inflammationmentioning
confidence: 99%
“…It is also present in resident macrophages, excluding Kupffer cells, and in tumor-associated macrophages (TAMs). Macrophages in inflamed or healing cardiac tissue also show expression of stabilin-1 [76][77][78][79][80][81]. Macrophages express stabilin-1 in response to IL-4 and dexamethasone, thus stabilin-1 is considered a marker of M2 polarization [82].…”
Section: Known Receptors and Target Cells Of Gdf-15mentioning
confidence: 99%
“…A phase II clinical trial testing Clever-1 inhibition using a humanized anti-Clever-1 antibody in 10 distinct, advanced solid tumor types (e.g., melanoma, pancreatic, liver cancer) already showed promising results ( 166 , 167 ). Finally, Clever-1 on TAMs was recently shown to be responsible for epidermal growth factor (EGF) clearance, a highly relevant tumor promoter ( 168 ).…”
Section: The Role Of Tumor-associated Macrophages In Hccmentioning
confidence: 99%
“…Preclinical studies showed that human monocytes expressing high levels of Clever-1 impaired Th1 T cell activation, which was reversed via siRNA knockdown or a blocking antibody (164) and that targeting Clever-1 in TAMs via macrophage-specific genetic knockout or via antibody blockade retarded the growth of LLC1 Lewis lung carcinoma cells in vivo, by inducing a robust CD8 T cell response (165). A phase II clinical trial testing Clever-1 inhibition using a humanized anti-Clever-1 antibody in 10 distinct, advanced solid tumor types (e.g., melanoma, pancreatic, liver cancer) already showed promising results (166,167). Finally, Clever-1 on TAMs was recently shown to be responsible for epidermal growth factor (EGF) clearance, a highly relevant tumor promoter (168).…”
Section: The Role Of Tumor-associated Macrophages In Hccmentioning
confidence: 99%